Organizational and Economic Problems in the Management of the Spiritual - Historical Development of Tourism in South Kazakhstan Region - Kuralbayev, Almas; Myrzaliev, Borash; Sevim, Burhan (International Review of Management and Marketing, 2016)
Nowadays the international market of tourist service is a great mechanism with many billion-dollar and fierce competition, so the priority is the definition of the tourist product, which is unique to Kazakhstan and features will be in demand. For the Republic of Kazakhstan the tourism industry is a top priority and here more attention to the development of inbound and domestic tourism was paid, development of exciting itineraries of cultural, environmental, equestrian and recreation areas. The new tourist brand of Kazakhstan was "At the crossroads of the worlds, in the center of Eurasia". The actuality of research by the fact that in the economy of Kazakhstan tourism is one of the most powerful factors that allow economies to develop, to introduce new technologies, to solve social problems is determined. That is why we often hear such features of tourism as "phenomenon of the twentieth century, the explosion of tourism", "tourism revolution". The purpose of the research is the formation of spiritual-historical, patriotic consciousness. The development of spiritual and educational sphere, preservation and efficient using of cultural heritage has particular significance for the history and culture of the region. Keywords: Management, tourism, Inbound tourism, Outbound tourism, Domestic tourism JEL Classifications: O18, Z30, Z39